2014
DOI: 10.3748/wjg.v20.i30.10525
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome in Southeastern Taiwan: Our experience with 11 cases

Abstract: Refeeding syndrome is an overlooked and risky disorder that has some potentially fatal complications. Nasogastric feeding in nursing homes is an important risk factor for patients and deserves greater attention based on the initial results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Table 2 summarizes the consensus on the different recommendations. Most of the clinical trials focusing on risk factors for RFS are in agreement with criteria proposed by the NICE guidelines [14,[29][30][31][32][33][34]. Still, Goyale [35] and Zeki [36] reported low sensitivity and specificity of these factors to predict RFS.…”
Section: Clinical Manifestations Of Rfsmentioning
confidence: 68%
“…Table 2 summarizes the consensus on the different recommendations. Most of the clinical trials focusing on risk factors for RFS are in agreement with criteria proposed by the NICE guidelines [14,[29][30][31][32][33][34]. Still, Goyale [35] and Zeki [36] reported low sensitivity and specificity of these factors to predict RFS.…”
Section: Clinical Manifestations Of Rfsmentioning
confidence: 68%
“…RFS was defined in a variety of ways in the eligible studies; however, this was not a focus point in this review, given the recent systematic review on this topic 1 . Hypophosphatemia was a primary or secondary outcome measure in 16 studies (see Supplementary table), with 6 of these using its presence as the sole clinical sign for RFS development 21‐26 . The most stringent criteria were used by Hofer et al, 6 Matthews et al, 8 and Matthews et al, 9 defining RFS as peripheral edema or acute circulatory overload, organ function disturbance including respiratory failure or pulmonary edema, and severely low electrolyte levels 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Half of the non–eating‐disorder studies (n = 7/13) reported the BMI of participants. Only 3 of these 24,33,34 had an average BMI in the underweight range (<19 kg/m 2 ) (see Table 1), with the remaining 4 studies reporting BMIs in a healthy to overweight range (BMI, 25–28 kg/m 2 ) 2,25,26,35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations